2014
DOI: 10.15407/fz60.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Acute L-glutamine deprivation affects the expression of TP53-related protein genes in U87 glioma cells

Abstract: Acute L-glutamine deprivation affects the expression of tP53-related protein genes in u87 glioma cells We have studied the effect of acute L-glutamine deprivation on the expression of tumor protein 53 (TP53)related genes such as TOPORS (topoisomerase I binding, arginine/serine-rich, E3 ubiquitin protein ligase), TP53BP1 (TP53 binding protein 1), TP53TG1 (TP53 inducible gene 1), SESN1 (p53 regulated PA26 nuclear protein), NME6 (NME/NM23 nucleoside diphosphate kinase 6), and ZMAT3 (zinc finger, Matrin-type 3) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
3
0
3
Order By: Relevance
“…Results of this study clearly demonstrated that the expression levels of almost all tested genes (E2F8, EPAS1, HOXC6,TBX3, TBX2, GTF2F2, GTF2B, MAZ, SNAI2,TCF3, and TCF8/ZEB1) encoding key proliferationrelated transcription factors, which are stress responsible and participate in malignant tumor growth, are affected by glucose and glutamine deprivations through IRE1 signaling branch of endoplasmic reticulum stress. Our results are confirmed to data that glycolysis and glutaminolysis are related to the control of cell proliferation through regulation of cell cycle and tumor suppressor genes [12,[38][39][40]. Recently we have shown that genes encoded transcription factorsE2F8, HOXC6, EPAS1, and TBX3are strongly depended from the endoplasmic reticulum stress particularly its IRE1 signaling pathway, because inhibition of IRE1, especially its endoribonuclease activity, significantly affects all these gene expressions.…”
Section: Discussionsupporting
confidence: 89%
“…Results of this study clearly demonstrated that the expression levels of almost all tested genes (E2F8, EPAS1, HOXC6,TBX3, TBX2, GTF2F2, GTF2B, MAZ, SNAI2,TCF3, and TCF8/ZEB1) encoding key proliferationrelated transcription factors, which are stress responsible and participate in malignant tumor growth, are affected by glucose and glutamine deprivations through IRE1 signaling branch of endoplasmic reticulum stress. Our results are confirmed to data that glycolysis and glutaminolysis are related to the control of cell proliferation through regulation of cell cycle and tumor suppressor genes [12,[38][39][40]. Recently we have shown that genes encoded transcription factorsE2F8, HOXC6, EPAS1, and TBX3are strongly depended from the endoplasmic reticulum stress particularly its IRE1 signaling pathway, because inhibition of IRE1, especially its endoribonuclease activity, significantly affects all these gene expressions.…”
Section: Discussionsupporting
confidence: 89%
“…Разом з тим, основним сенсорно-сигналь-ним шляхом реалізації ефектів стресу ендо-плазматичного ретикулума на ріст злоякісних огляДи пухлин є ERN1, причому він дуже тісно пов'язаний також із гіпоксією та ішемією [17,49,50,55,57,62,63]. Це було чітко продемон-стровано на клітинах гліоми, найагресивніших із відомих злоякісних пухлин із вираженим ангіогенезом та посиленою інвазією клітин у нормальну паренхіму головного мозку [45, 53,64,65].…”
Section: рис 3 схематичне зображення структури Ern1 в ендоплазматичunclassified
“…На рис. 4 на-ведено схематичне зображення структури комплементарної ДНК ERN1 та її змінених варіантів: без ензиматичної активності та з мутацією в ендорибонуклеазному домені на основі раніше опублікованих даних [62,66]. ефективність пригнічення функції сиг-нального ензиму ERN1 у клітинах гліоми оцінювали за рівнем фосфорильованої форми ERN1 та експресії альтернативного сплайс-варіанта мРНК XBP1 (XBP1s) в умовах стресу ендоплазматичного ретикулума, індукованого тунікаміцином.…”
Section: рис 3 схематичне зображення структури Ern1 в ендоплазматичunclassified
See 1 more Smart Citation
“…Ablation of IRE1 function has been shown to result in a significant anti-proliferative effect in glioma growth through down-regulation of prevalent pro-angiogenic factors and up-regulation of antiangiogenic genes as well as by modification of these genes expression by glutamine deprivation [20,25]. Malignant gliomas are highly aggressive tumors with very poor prognosis and to date there is no efficient treatment available.…”
mentioning
confidence: 99%